Characterization of Subarachnoid Hyperdensities After Thrombectomy for Acute Stroke Using Dual-Energy CT. (8th February 2022) - Renú, Arturo; Laredo, Carlos; Rodríguez-Vázquez, Alejandro; Santana, Daniel; Werner, Mariano; Llull, Laura; Lopez-Rueda, Antonio; Urra, Xabier; Rudilosso, Salvatore; Obach, Víctor; Amaro, Sergi; Chamorro, Ángel
Abstract : Background and Objectives: The presence of postinterventional subarachnoid hyperdensities (SA-HD) is a relatively common finding after mechanical thrombectomy (MT). We aimed to assess the incidence, characteristics, clinical relevance, and predictors of SA-HD after MT as categorized through the use of postinterventional dual-energy CT (DE-CT). Methods: A single-center consecutive series of patients with acute stroke treated with MT was retrospectively reviewed. Posttreatment SA-HD were defined as incident extraaxial hyperdensities in a follow-up DE-CT performed within a median of 8 hours after MT. SA-HD were further classified according to their content (isolated contrast extravasation vs blood extravasation) and extension (diffuse [hyperdensities in more than one extraparenchymal compartment] vs nondiffuse). Adjusted logistic regression models assessed the association of SA-HD with pretreatment and procedural variables and with poor clinical outcome (shift towards worse categories in the ordinal Rankin Scale at 90 days). Results: SA-HD were observed in 120 (28%) of the 424 included patients (isolated contrast extravasation n = 22, blood extravasation n = 98). In this group, SA-HD were diffuse in 72 (60%) patients (isolated contrast extravasation n = 7, blood extravasation n = 65) and nondiffuse in 48 (40%) patients (isolated contrast extravasation n = 15, blood extravasation n = 33). Diffuse SA-HD were significantly associated with worse clinical outcome in adjusted models (common odds ratio [cOR] 2.3, 95% confidence interval [CI] 1.36–4.00, p = 0.002), unlike the specific SA-HD content alone. In contrast with the absence of SA-HD, only the diffuse pattern with blood extravasation was significantly associated with worse clinical outcome (cOR 2.4, 95% CI 1.36–4.15, p = 0.002). Diffuse SA-HD patterns were predicted by M2 occlusions, more thrombectomy passes, and concurrent parenchymal hematomas. Discussion: In our cohort of patients imaged within a median of 8 hours after MT, postinterventional SA-HD showed a diffuse pattern in 17% of thrombectomies and were associated with more arduous procedures. Diffuse SA-HD but not local collections of blood or contrast extravasations were associated with an increased risk of poor outcome and death. These findings reinforce the need for improvement in reperfusion strategies. Classification of Evidence: This study provides Class IV evidence that in individuals with proximal carotid artery territory occlusions treated with MT, diffuse postinterventional SA-HD on imaging 8 hours postprocedure are associated with worse clinical outcomes at 90 days.